Towards a Video Consumer Leaning Spectrum: A Medium-Centric Approach - Chan-Olmsted, Sylvia; Wolter, Lisa-Charlotte; Adam, Elisa Dorothee (Nordic Journal of Media Management, 2020)
Purpose: As TV and digital video converge, there is a need to compare advertising effectiveness, advertising receptivity, and video consumption drivers in this new context. Considering the emerging viewing practices and underlying theories, this study examines the feasibility of the traditional notion of differentiating between lean-back (LB) and lean-forward (LF) media, and proposes a revised approach of addressing video consumption processes and associated advertising effectiveness implications. Methodology: An extensive, systematic literature review examines a total of 715 sources regarding current lean-back/lean-forward media research and alternative approaches as by (1) basic terminologies, (2) limitations of lean-back/lean-forward situations, (3) advertising effectiveness implications, (4) video-specific approaches. Findings/Contribution: Key differences between lean-back and lean-forward video consumption are presented. A conceptual integration of video ad receptivity/effectiveness drivers is proposed to guide future media and marketing research and practice. Video consumption today is no longer lean-back or lean-forward, but a “leaning spectrum” with two dimensions: leaning direction and leaning degree. Designing video content today requires focusing on consumption drivers and platform synergies for owning the “leaning spectrum”.